The Impact of Demographic Factors on MSME Tax Compliance in Pontianak City - Afif, Ali; Setiawan, Aris (Journal of Business & Management, 2024)
The research aims to find out whether demographic factors are associated with tax understanding and knowledge, both regulations and policies implemented by the government on tax compliance for MSMEs in the city of Pontianak. This study used primary data by distributing questionnaires in Pontianak City. The sample used in this study is individual taxpayers who own MSMEs in Pontianak City. The research method uses statistical tests with processing techniques and data analysis using data quality tests and classical assumption tests and multiple regression. The results of the study found that age and gender had no effect on tax compliance, because it returned to the awareness of each individual that taxes were important